Survey on synergism effect of ketotifen in combination with pyrimethamine in treatment of acute murine toxoplasmosis - Montazeri, Mahbobeh (Trop Med Health, 2017)
BACKGROUND: Standard treatment of toxoplasmosis is accompanied by severe side effects and low tolerability; accordingly, alternative medicines are critically needed. Ketotifen (KET) as a cell membrane stabilizer could be an appropriate inhibitor of Toxoplasma gondii (T. gondii) parasite entrance into the host cells. Therefore, the focus of current study is characterization of the anti-Toxoplasma activity of KET in the acute phase of toxoplasmosis in murine model as pre-treatment and post-treatment (before and after infection with RH strain). KET was used intraperitoneally both individually (2 and 3 mg/kg/day) and in combination with pyrimethamine (PYR) (50 mg/kg/day). One week after the post infection, DNA was extracted from brain biopsies samples. Parasite load was calculated using Quantitative-PCR (Q-PCR) in a triplicate reaction for each DNA with the target for at RE (a 529 bp repeat element) gene. RESULTS: A significant difference between KET and control groups was observed (P < 0.001) in the pre-treatment and post-treatment groups. Both KET and the combination of KET and PYR showed a reduction in the parasite load in brain through the acute phase of the infection. 2 mg/kg/day dose of KET resulted in higher anti-Toxoplasma activity (15,698 parasites/ml) compared to 3 mg/kg/day dose of KET (72,898 parasites/ml) in brain in the pre-treatment group. In addition, KET combined with PYR significantly decreased the parasite load in the post-treatment group. CONCLUSIONS: Our results indicated that KET has both prophylactic and therapeutic effects on acute phases of the disease.